Analisis Pengaruh Content Digital Marketing terhadap Keputusan Pembelian Pengguna Tiktok di Kalangan Mahasiswa Kota Bandung - Amanda Maharani, Afifah Indira (International Journal Administration, Business & Organization, 2023)
This research aims to determine the influence of digital marketing content on consumer purchasing decisions of TikTok users among students in the city of Bandung, Indonesia using data collection techniques using Google Form media which was distributed to 105 respondents. The results of this research show that Content Digital Marketing has a significant influence on Consumer Purchasing Decisions of TikTok Users among students in Bandung City, Indonesia.